166k views
0 votes
ASAP GUYS PLEASE I NEED UR HELP THIS IS SO HARD
Solve: 5 − 7 ( z + 1 ) = 7 ( − 9 − 3 z )

2 Answers

6 votes
  • 5-7(z+1)=7(-9-3z)
  • 5-7z-7=-63-21z
  • -2-7z=-63-21z
  • 2+7z=63+21z
  • -61=14z
  • z=-61/14
User Treckstar
by
4.3k points
0 votes

Answer:


-(61)/(14)

Explanation:

Question: 5 - 7(z+1) = 7(-9-3z)

We multiply the number in front of the bracket first, since that is multiplication.

--> 5 -7z -7 = -63 - 21z

--> -7z -2 = -63 - 21z

Now, we move all the z and all the numbers to each side.

--> -7z +21z = -63 +2

--> 14z = -61

--> z = -61/14

This cannot be simplified further, so z is -61/14.

User Kirill Yunussov
by
4.9k points